Metode Pemecahan Kontradiksi Dalil dalam Kitab Jam’u al-Jawami’ - Afrohah, Afrohah (Fakultas Syariah INSURI Ponorogo, 2021)
People today we see a view that occurs among Muslims. This difference arises because of the arguments that are textually contradictory to one another, whether in the Koran, hadith or other arguments. The science of Ushul Fiqih discusses it in a special chapter, namely the Ta'arud Al Adillah chapter (Contradiction of the Dalil), which is a chapter that studies and examines textually contradicting arguments and then makes settlement steps or methods. There are a lot of Islamic legal experts who discuss Ta'arud Al Adillah, but to be more focused the author will only discuss the